(untitled) (Journal of the Asiatic Society of Bangladesh, Humanities, 2025)
Ecocriticism is an emerging arena of literary criticism that questions humans’ anthropocentric tendency to dominate nature. This study scrutinizes Bangla writer Bibhutibhushan Bandyopadhyay’s novel Aranyak (1939) from the ecocritical perspective. The Bangla novel Aranyak was translated into English by Rimli Bhattacharya in 2002, and she titled the translated novel Aranyak: Of the Forest. A qualitative textual analysis approach is adopted to conduct this study. Primary data is collected from the translated version of the novel. This study also gathers required information from several authentic sources, such as journals, newspapers, websites, and books. The novel revolves around the central character Satyacharan, who works as an estate manager. Satyacharan’s anthropocentric tendency is expressed throughout the novel since his only task is to lease the forests among the tenants. In an exceptional way, Satyacharan’s biocentric feeling also develops with time when he feels that he is accountable for the ecological apocalypse. At the end of the novel, Bibhutibhushan emphasizes a biocentric view as all forms of things (living and nonliving) possess intrinsic value. Aranyak is a narrative of giving up contemporary urban life in an effort to return to nature and rejuvenate oneself. Overall, Aranyak is about a city man falling in love with the forests. A melancholic tone of reminiscence and repentance focusing on environmental destruction adds a profound depth to Aranyak’s plot. JASBH, Vol. 70(1), June 2025, pp. 109-122